2015
DOI: 10.1179/2047773215y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Use of a clinical tool for screening and diagnosis of cutaneous leishmaniasis in Sri Lanka

Abstract: Cutaneous leishmaniasis (CL) was first detected in Sri Lanka in 1992.Local disease is caused by a genetically different variant of Leishmania donovani. Early case detection and management is the mainstay of L. donovani control. High degree of clinical suspicion is critical but a clinical diagnostic tool is not available for leishmaniasis. Current study described, for the first time, a two-staged clinical algorhythm that facilitates screening of CL in Sri Lanka by primary health care worker in stage 1 and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…When the diagnostic purpose is to detect Leishmania genus-specific DNA in skin biopsy samples, either ITS1 PCR with LITSR/L5.8S primers or Leishmania KDNA primers JW11/12 would be successful due to a 92% sensitivity and 100% specificity shown in the study. Our study emphasises the importance of laboratory-based in addition to clinical diagnosis of CL as suggested by Siriwardana et al (2015 ). An interesting conclusion, to be confirmed by larger sample size studies, is that L. donovani is the only species causing polymorphic clinical presentations in Sri Lanka.…”
Section: Discussionmentioning
confidence: 68%
“…When the diagnostic purpose is to detect Leishmania genus-specific DNA in skin biopsy samples, either ITS1 PCR with LITSR/L5.8S primers or Leishmania KDNA primers JW11/12 would be successful due to a 92% sensitivity and 100% specificity shown in the study. Our study emphasises the importance of laboratory-based in addition to clinical diagnosis of CL as suggested by Siriwardana et al (2015 ). An interesting conclusion, to be confirmed by larger sample size studies, is that L. donovani is the only species causing polymorphic clinical presentations in Sri Lanka.…”
Section: Discussionmentioning
confidence: 68%
“…Further analysis revealed that soldiers represented a single age group (21–30 years), probably reflecting the age distribution within their occupation, while civilians were of a wider age range (data not shown). Previous studies have reported higher involvement of age group of 21–40 years with CL as compared to other age groups [ 19 ]. There may be variation in antibody response patterns in Leishmania strains or patient populations prevalent in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the availability of such a tool is important for the detection of microscopy negative cases. Currently, IVC and polymerase chain reaction (PCR) are used with limited availability for the diagnosis of such cases in Sri Lanka [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%